HEISENBERG-PAULI-WEYL INEQUALITY IN MORREY SPACES - WAJIH (NIM: 20116028), ASYRAF
In this thesis we prove a generalized of Heisenberg-Pauli-Weyl inequality in Morrey spaces by using the boundedness of fractional integral operators on Morrey spaces and interpolation theory relating to the fractional power of Laplacia.